Education markets and schools’ mechanisms of exclusion: The case of Chile - Zancajo, Adrián (Education Policy Analysis Archives, 2019)
Education market advocates frequently argue that socioeconomically disadvantaged students could be the main beneficiaries of privatization and market policies. However, the international evidence has shown how privatization and pro-market policies have a negative impact in terms of equity, which particularly affect socioeconomically disadvantaged populations, increase school segregation and stratification, and foster educational inequalities. The main objective of this paper is to analyze how the responses developed by educational providers in marketized environments especially impact poor populations and can act as mechanisms of exclusion. In this context, Chile is an optimal case study due to the extreme version of privatization and market policies it adopted four decades ago. Based on the case study of two municipalities in Chile, which represent two local education markets, the presented evidence combines in-depth interviews with school principals and families. The paper analyses how schools’ responses in the context of a competitive environment produce, among other effects, processes of exclusion affecting students from low socioeconomic backgrounds, foster school segregation and increase educational inequalities. Finally, the paper elaborates on the limits of education markets and privatization policies, as well as market regulation reforms, in providing better educational opportunities to socioeconomically disadvantaged students.